1996
DOI: 10.1039/cc9960001401
|View full text |Cite
|
Sign up to set email alerts
|

Laying traps for elusive prey: recent advances in the non-covalent binding of anions

Abstract: The structure and function of a new class of host molecules for the supramolecular complexation of anionic guest species are analysed within the context of other recent advances in the field. In particular, organometallic hosts based upon the calixarenes, and the related macrocycle cyclotriveratrylene (CTV), are examined. X-Ray crystallographic results clearly demonstrate the inclusion of anionic guest species such as BF4-, I-, CF3S03-, Re04-etc. within the ostensibly electron-rich bowl-shaped cavities of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
149
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 47 publications
1
149
0
2
Order By: Relevance
“…Anion supramolecular chemistry involves the development and use of selective anion receptors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In fact, today a large number of coordination studies can be found in the literature describing a wide range of different ligands for anion coordination mainly involving hydrogen bonding, [15][16][17][18][19] electrostatic interactions [20][21][22][23][24][25][26][27] or coordination with suitable metal cations. [28][29][30][31][32][33] The nature of the binding sites and their specific spatial arrangement determine the binding constant with a certain anion and usually selective coordination can be found when a large host-guest complementarity is reached.…”
Section: -Introductionmentioning
confidence: 99%
“…Anion supramolecular chemistry involves the development and use of selective anion receptors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In fact, today a large number of coordination studies can be found in the literature describing a wide range of different ligands for anion coordination mainly involving hydrogen bonding, [15][16][17][18][19] electrostatic interactions [20][21][22][23][24][25][26][27] or coordination with suitable metal cations. [28][29][30][31][32][33] The nature of the binding sites and their specific spatial arrangement determine the binding constant with a certain anion and usually selective coordination can be found when a large host-guest complementarity is reached.…”
Section: -Introductionmentioning
confidence: 99%
“…We recently reported the synthesis and anion binding of urea-functionalized calix [4]diquinone, 20,21 and also the synthesis and the cation binding of diesteranthraquinone. 26 In this paper we report the binding properties of ureaanthraquinone toward H 2 PO 4 − against some anions such as CH 3 (2) under nitrogen atmosphere and refluxed for 2 hrs. The solvent was removed and the residue treated with 10 mL of 2 M HCl and refluxed for 1 hr.…”
Section: Introductionmentioning
confidence: 99%
“…2 Selective complexation of anions is more demanding than that of cations in the view of the higher free energies of solvation of anions and the pH dependence of anion complexation. 3 Neutral ferrocene receptors, [4][5][6][7] thiouronium receptors, 8 neutral bisthiourea or bisurea hosts, [9][10][11][12] and porphyrin receptors 13 were investigated for selective recognition of H 2 PO 4 − anion. A selective complexation of Cl − , Br − or I − can be achieved by the neutral urea receptors derived from the lower rim of calix [4]arene, 14 and three urea groups at the lower rim of calix [6]arene are well suited for complexation of tricarboxylate.…”
Section: Introductionmentioning
confidence: 99%
“…Selective complexation of anions is also more demanding than that of cations a result of the higher free solvation energies of anions, the low charge density of anions, and the pH dependence of anion complexation. 1,2 Accompanied by the development of ionselective electrodes (ISEs), the selective determination of many anions has a crucial drawback --the classical Hofmeister series, which is correlated with a preference for hydrophobic anions. Therefore, the need for ionophores with improved selectivities and sensitivities in the field of anionselective electrodes increases.…”
Section: Introductionmentioning
confidence: 99%